Export and digitization of agro-exporting companies in Lima, Peru, 2023 - Parque-Flores, Sandy Melissa (2024)
The agro-export sector in Lima, Peru, is essential to the local economy due to its strategic location and favorable climate. However, to remain competitive and expand internationally, these companies must adapt to new technologies in an increasingly digitized world. The objective of this study was to identify the relationship between exports and digitalization in agroexporting companies in Lima, Peru, 2023.  The method used was the cross-sectional quantitative study approach, whose design is non-experimental, it is also correlational in scope, a survey-type instrument was used to 130 agro-exporting companies in which non-probabilistic, simple random sampling by convenience was used. As a result, it was observed that exports are positively related to the digitalization of agro-exporting companies in Lima, Peru, 2023. It was concluded that if exports increase, digitalization increases in the same proportion.